Application of MgSO4 • 7H2O and Fly Ash as a Reinforcement in the Matrix of Solid Ceramic Units (2018)
Chemical compositions obtained by XRF from clay and fly ash from coal combustion in a hive furnace are reported. The quantities of clay, fly ash and magnesium sulphate (MgSO4 · 7H2O) were selected according to their chemical composition to achieve total efflorescence on the surface of the brick (solid ceramic unit). Once the masonry units were formed by pressing, they were treated at 400 °C for two hours to remove moisture, and once they reached 950 °C, they were cooked at this temperature for three hours. The chemical composition of the efflorescence on the surface of the specimens was established by XRF, the cross section of a brick was morphologically analyzed and, finally, the specimens were subjected to compression tests to determine their resistance and maximum water absorption, taking into account Colombian technical standard NTC 4205.